2002
DOI: 10.1002/cjce.5450800113
|View full text |Cite
|
Sign up to set email alerts
|

An apparatus for the measurement of surface tensions at high pressures and temperatures

Abstract: NCUT Natural Resources Canada, Devon, AB T9G lA8, Canada ydrocracking and hydrotreating of heavy petroleum fractions or of hydrocarbon liquids that require desulfurization and/or H denitrification is one of today's major and now quite mature technologies. The reactions of hydrocracking, hydrodesulfurization (HDS) or hydrodenitrification (HDN) are usually carried out at relatively high temperatures (350'C to 45OOC) and high hydrogen pressures of up to 15 or 20 MPa. In most of these processes, a solid catalyst i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…We have chosen to use the pendant drop technique for measuring gas-water IFT since it is the most adaptable method not only for high pressure conditions, but also for a wide range of temperatures (Michaels and Hauser, 1951;Adamson, 1960;Millette, et al, 2002). Unlike other IFT measurement techniques that are empirically derived or require corrections applied to the measured data, the pendant drop approach is an absolute method based on a mathematical solution to the Young-Laplace equation (Deam and Maddox, 1970).…”
Section: Pendant Drop Method: Theory and Practicementioning
confidence: 99%
“…We have chosen to use the pendant drop technique for measuring gas-water IFT since it is the most adaptable method not only for high pressure conditions, but also for a wide range of temperatures (Michaels and Hauser, 1951;Adamson, 1960;Millette, et al, 2002). Unlike other IFT measurement techniques that are empirically derived or require corrections applied to the measured data, the pendant drop approach is an absolute method based on a mathematical solution to the Young-Laplace equation (Deam and Maddox, 1970).…”
Section: Pendant Drop Method: Theory and Practicementioning
confidence: 99%
“…Millette et al 7) suggested the use of the maximum bubble pressure method for measuring surface tension at high pressures in opaque liquids. This method is based on the pressure required to create a bubble at the tip of a capillary tube, which is related to the surface tension and the bubble radius: (4) where r is the radius of the bubble.…”
Section: Surface Tensionmentioning
confidence: 99%
“…The use of two submerged capillaries of different radii allows correction for hydrostatic head, and a correction is used for non-spherical bubble formation at the tip of a capillary. Millette et al 7) reported calibration data on n-octane to 225°C at 13.8 MPa, and claimed useful results on oils up to 350°C. Unfortunately, neither the data nor the validation for the higher temperature results were presented.…”
Section: Surface Tensionmentioning
confidence: 99%
“…The apparatus is shown in Figure 1, and details of its construction, and its operation can be found in our previous publication (Millette et al, 2002). Tests with the two bitumen samples were done in the temperature range of 185° to 350°C to obtain a suffi ciently fl uid sample at the lower temperature, and to avoid thermal cracking at the higher temperature.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Because no suitable apparatus appeared to have been developed capable of such measurements, the initial part of the work required a survey of existing methods, and the selection and development of one of thesethe maximum bubble pressure method-as one capable of operation at temperatures to 450°C and pressures to 14 MPa. This initial phase of the study has been described earlier (Millette et al, 2002), and the present report gives the results of surface tension measurements on a number of pure paraffi nic hydrocarbons, two highly saturated petroleum cuts, and two heavy oil feeds-an Athabasca coker feed and a Cold Lake vacuum bottoms fraction-both from the northern Alberta bitumen deposits.…”
mentioning
confidence: 98%